An Empirically Derived Taxonomy of Biopsychosocial Factors of Adjustment to Fibromyalgia: Results of a Multivariate Analysis. (October 2020) - Muller, Veronica; Chan, Fong; Iwanaga, Kanako; Wu, Jia-Rung; Chen, Xiangli; Lee, Beatrice; Tao, Jing; Rumrill, Phillip; Bezyak, Jill
Fibromyalgia (FM) is a lifelong central nervous system disorder that is precipitated by a range of biological, psycho-cognitive, and social factors. The aims of this exploratory study were to (a) identify biopsychosocial and cognitive factors that may affect an individual's response to FM, (b) determine whether individuals with FM can be grouped into homogeneous subgroups based on biopsychosocial factors associated with response to FM, and (c) compare subgroup differences in health outcomes and life satisfaction. This study included 302 participants with FM. Principal components analysis yielded three sets of biopsychosocial factors that may affect response to FM (i.e., protective, cognitive-affective, and physical factors). Based on these three factors, a cluster analysis was performed, which produced three homogeneous subgroups: (a) the moderate amount of problems group, (b) the least amount of problems group, and (c) the many problems group. Analysis of variance (ANOVA) results indicated that these three subgroups differed significantly in terms of health outcomes and life satisfaction. The findings of this study broaden the existing literature related to understanding FM from a multidimensional symptom response perspective and contribute to the development and validation of biopsychosocial interventions for people with FM.